Idiopathic Pulmonary Fibrosis: What do we Know about the Role of Occupational and Environmental Determinants? A Systematic Literature Review and Meta-Analysis. (3rd October 2022) - Pauchet, A.; Chaussavoine, A.; Pairon, JC; Gabillon, C.; Didier, A.; Baldi, I.; Esquirol, Y.
ABSTRACT: The objectives of this systematic review of original articles published up until August 2021 and meta-analyses were to identify the links between occupational and non-occupational environmental exposures, types of occupations and idiopathic pulmonary fibrosis (IPF). Sixteen selected case-control studies were qualified as good level with Newcastle-Ottawa quality assessment scale. Sensitivity analyses highlighted the role of choice of control group, tobacco adjustment and diagnostic tools. Significantly increased risks of IPF were observed (OR (95%CI): for metals (1.42(1.05–1.92)), wood (OR:1.32(1.02–1.71)), and general dust (OR:1.32(1.08–1.63)) exposures. Subgroup analyses found a significantly elevated risk for: hardwood (OR:1.75 (1.13–2.70)), organic dusts (OR:1.72 (1.20–2.46)) and pesticides (OR:2.30 (1.30–4.08)), while no significant change was noted for softwoods and solvents. Smoking adjustments: general dust (1.45 (1.04–2.03)/organic dust (2.5 (1.49–4.22)/metals (1.87 (1.16–3)/wood dust OR: 1.16 (0.86–1.61)/pesticide exposure 2.4 (0.84–6.9) were calculated. Among agricultural workers, the risk was also increased (OR:2.06 (1.02–4.16)). Few environmental data were available and no significant associations detected. Thus, these meta-analyses highlighted the role of some occupational exposures in IPF occurrence. A more accurate and thorough assessment of exposures over the entire working life as well as on the duration and intensity of exposure and complex of multi-pollutant exposure is needed in future research and clinical practice. Graphical Abstract: uf0001